2017
DOI: 10.1073/pnas.1613405114
|View full text |Cite
|
Sign up to set email alerts
|

Tissue dual RNA-seq allows fast discovery of infection-specific functions and riboregulators shaping host–pathogen transcriptomes

Abstract: Pathogenic bacteria need to rapidly adjust their virulence and fitness program to prevent eradication by the host. So far, underlying adaptation processes that drive pathogenesis have mostly been studied in vitro, neglecting the true complexity of host-induced stimuli acting on the invading pathogen. In this study, we developed an unbiased experimental approach that allows simultaneous monitoring of genome-wide infection-linked transcriptional alterations of the host and colonizing extracellular pathogens. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
119
4
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 137 publications
(131 citation statements)
references
References 100 publications
(106 reference statements)
5
119
4
3
Order By: Relevance
“…Whereas pathogens can adapt central metabolic pathways to the respective available carbon and nitrogen sources,h osts have developed efficient means to limit the availability of essential metal ions.This is reflected in in vivo transcriptomic studies of bacteria from infection sites of animal models.T he bacteria in these studies showed astress response to metal-ion limitation. [5][6][7] Thebest studied example is the dependence of pathogens on iron, [8] and so most research approaches aiming at exploiting nutritional immunity as atherapeutic target address the iron acquisition systems.T his is the reason why iron acquisition systems and their respective chemical inhibitors are described predominantly in this Review,b ut where possible we also include chemical approaches to influence the uptake of other metal ions.F or various other aspects related to nutritional immunity,t he recent reviews on microbiological aspects, [9,10] the coordination chemistry of siderophores, [11] environmental applications of siderophores, [12] zinc homeostasis, [9,13] and the chemical synthesis of antibacterials [14] are highly recommended. More specific reviews can be found in the following chapters.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas pathogens can adapt central metabolic pathways to the respective available carbon and nitrogen sources,h osts have developed efficient means to limit the availability of essential metal ions.This is reflected in in vivo transcriptomic studies of bacteria from infection sites of animal models.T he bacteria in these studies showed astress response to metal-ion limitation. [5][6][7] Thebest studied example is the dependence of pathogens on iron, [8] and so most research approaches aiming at exploiting nutritional immunity as atherapeutic target address the iron acquisition systems.T his is the reason why iron acquisition systems and their respective chemical inhibitors are described predominantly in this Review,b ut where possible we also include chemical approaches to influence the uptake of other metal ions.F or various other aspects related to nutritional immunity,t he recent reviews on microbiological aspects, [9,10] the coordination chemistry of siderophores, [11] environmental applications of siderophores, [12] zinc homeostasis, [9,13] and the chemical synthesis of antibacterials [14] are highly recommended. More specific reviews can be found in the following chapters.…”
Section: Introductionmentioning
confidence: 99%
“…Baulamycin A( 5a)i st die aktivere der beiden Substanzen und inhibiert die Enzyme AsbA und SbnE mit IC 50 -Werten von 180 mm und 4.8 mm (Abbildung 4). Diese Enzyme katalysieren die Konjugation von Spermidin (9)oder l-2,3-Diaminopropionsäure (10)m it Citrat (8)w ährend der Biosynthese der Siderophore Staphyloferrin (6)u nd Petrobactin (7).…”
Section: Eisenaufnahme:e Inunclassified
“…[5][6][7] Das am besten studierte Beispiel ist die Abhängigkeit von Pathogenen von Eisen, [8] sodass die meisten Forschungsansätze,d ie die Ausnutzung der Nährstoffimmunitätf ürt herapeutische Ansätze zum Ziel haben, sich mit Eisenaufnahmesystemen beschäftigen. Daher gehçrt es zur ersten Verteidigungsstrategie des Wirtes gegen Infektionen, dem Pathogen Nährstoffe zu entziehen, ein Phänomen, das als Nährstoffimmunitäto der "nutritional immunity" bezeichnet wird.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…In another study, Peyer's patches from mice infected with Yersinia pseudotuberculosis were analyzed [52]. In both examples, infected tissues were isolated and homogenized prior to total RNA extraction for sequencing.…”
Section: Figure 1| Macromolecular Differences Between Cells Of Eukarymentioning
confidence: 99%